If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y+2)=15
We move all terms to the left:
6(y+2)-(15)=0
We multiply parentheses
6y+12-15=0
We add all the numbers together, and all the variables
6y-3=0
We move all terms containing y to the left, all other terms to the right
6y=3
y=3/6
y=1/2
| 6(g-2)=24 | | -4=b/4 | | 7+d=-10 | | 12=-8y+4(y+7) | | 40=5x8 | | 2(-9x+4)=-18x+16 | | 2-3x=-x=8 | | 3(x-8)+15=36 | | -25x=-5(5x-1) | | -1112x=+121 | | 2(v+1.6)+1.42=17.02 | | j/3+2=0 | | 6q+6=84 | | 10z=-6+6(-5z+1) | | s+3s-8=180 | | 7x-10=3x-30 | | -3+3x-4=6(x+2)+8 | | 2(j+16)=-4 | | g-7=81-7g | | 8x-6=-12x+34 | | 3h-6=45 | | 5.00-0.65m=10.00-0.45m | | 3/5+x=21/0 | | 89+x+37=180 | | 3x+(1x+2)+11x=1/2(4x+8) | | 3t^2+4t+8=-6 | | -6(7k-6)=-6-3(6k+10) | | 6(n=4+8)−5n=4 | | 2x+3(4x-)=8-3x | | -w/5=46 | | 2(t-6)-10=-6 | | 5x2-27=4x2-6x |